Optimizing geothermal production in fractured rock reservoirs under uncertainty. (November 2020) - Patterson, Jeremy R.; Cardiff, Michael; Feigl, Kurt L.
Highlights: A combination of simple analytical models and optimization under uncertainty produces reasonable profit forecasts and highlights key sensitive parameters. Increasing the surface area for heat transfer increases the thermal and financial sustainability of a geothermal reservoir. Sensitivity analysis shows that effective reservoir transmissivity and well spacing exert the largest controls on the financial performance of the reservoir. Abstract: Geothermal energy resources are highly available but under-utilized throughout the world. Previous studies have sought to understand reservoir response to geothermal production and optimize production rates to maximize lifetime profits of geothermal reservoirs; however, these studies largely overlook the uncertainty in subsurface structure, such as the number of preferential flow pathways (e.g., fractures) that are available for fluid and heat transport. We present a combination of simple analytical models that maximize the profits of an idealized synthetic geothermal reservoir, while considering reservoir structural uncertainty, using expected net present value. For a typical case, we find that effective reservoir transmissivity and inter-well spacing exert the largest controls on the lifetime profitability of an idealized geothermal reservoir, and for a given reservoir there exists a critical number of hydraulically active fractures beyond which additional fractures provide no increase in lifetime profits. Given initial reservoir characterization data, our model simulates reservoir performance that predicts financial outcomes, which operators can use during initial exploration stage. These predictions are also useful during normal operations to consider strategies, such as drilling make-up wells, to mitigate the effects of production-induced thermal drawdown.